2022
DOI: 10.1126/science.abd0966
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast water permeation through nanochannels with a densely fluorous interior surface

Abstract: Ultrafast water permeation in aquaporins is promoted by their hydrophobic interior surface. Polytetrafluoroethylene has a dense fluorine surface, leading to its strong water repellence. We report a series of fluorous oligoamide nanorings with interior diameters ranging from 0.9 to 1.9 nanometers. These nanorings undergo supramolecular polymerization in phospholipid bilayer membranes to form fluorous nanochannels, the interior walls of which are densely covered with fluorine atoms. The nanochannel with the smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
131
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(134 citation statements)
references
References 72 publications
3
131
0
Order By: Relevance
“…Notably, Itoh et al showed that the 0.9 nm channels exhibit a water permeation flux two orders of magnitude higher than those of aquaporins and carbon nanotubes. 21 It should be noted that the covalent oligoamide nanorings are rather more robust compared to the weakly coordinated hexameric assemblies reported in our work. Nevertheless, these results indicate that the incorporation of CF 3 groups can promote highly hydrophobic molecu-lar and supramolecular nanochannels with fluorine-rich interior walls.…”
mentioning
confidence: 47%
“…Notably, Itoh et al showed that the 0.9 nm channels exhibit a water permeation flux two orders of magnitude higher than those of aquaporins and carbon nanotubes. 21 It should be noted that the covalent oligoamide nanorings are rather more robust compared to the weakly coordinated hexameric assemblies reported in our work. Nevertheless, these results indicate that the incorporation of CF 3 groups can promote highly hydrophobic molecu-lar and supramolecular nanochannels with fluorine-rich interior walls.…”
mentioning
confidence: 47%
“…Creating microholes on the PPy surface through a surface templating technique has been used to increase the strain rate of the PPy actuator ( 43 ). In another study, nanochannels with hydrophobic interior surfaces have been demonstrated to greatly increase the liquid transportation speed ( 44 ). Such nanochannels have the potential to boost the ion diffusion rate into the polymer matrix, thus increasing the actuator’s beating frequency.…”
Section: Discussionmentioning
confidence: 99%
“…Another recent study on fluorous nanochannels (NCs) by Aida and co-workers also seems to support this new direction in channel design. They developed a series of nanochannels (NCs) with different pore sizes that are 9 Å ( F12 NC 4 ), 14.6 Å ( F15 NC 5 ), 17.6 Å ( F18 NC 6 ), and 19 Å ( F12 NC 6 ), by stacking polyamide-based nanorings (NRs) with perfluorinated functional groups (Figure C) within lipid bilayers . All NCs reported showed significantly improved water permeability over AQP1 by a factor of up to ∼10 3 .…”
Section: Recent Developments In Awc Designmentioning
confidence: 99%
“…Rather, F···H–O–H interaction disrupts tetrahedral H-bond networks of surrounding water molecules, breaking down water nanoclusters into even smaller aggregates (Figure D). , Those small clusters are proposed to “slide through together” with reduced viscous shear stresses. It is also interesting to note that, compared to the single-walled carbon nanotube that has a 5 Å pore diameter that transports water with a 1D wire configuration, carbon nanotubes with 8 Å (CNTP-8) pore diameter showed an order lower water permeability but fluorinated NCs with 9 Å diameter ( F12 NC 4 ) showed 3 orders of higher permeability, whereas both CNTP-8 and F12 NC 4 transport water as clusters, and not in the classical single-file profile.…”
Section: Recent Developments In Awc Designmentioning
confidence: 99%
See 1 more Smart Citation